2016
DOI: 10.21608/jfds.2016.42769
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality and Safety of Commercial Market Yogurt in Giza, Egypt

Abstract: Yogurt is the most popular dairy product in Egypt. The popularity of yogurt can be attributed to its sensory characteristics and nutritional value. The microbiological characteristics of yogurt also contribute greatly to the quality and shelf life of the final product. One hundred yogurt samples were collected from local market stores and were examined for their culture viability of lactic acid bacteria (Lactobacillus spp. and Streptococcus spp.), Bacillus spp., psychrophilic bacteria (Pseudomonas spp.), patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Lactobacillus casei was selected as LAB bacteria strain in our study among twenty-five lactic acid bacteria were collected and identified (13). Lactobacillus casei was assessed for probiotic properties to fulfill the desirable criteria to be applied (Table 1).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Lactobacillus casei was selected as LAB bacteria strain in our study among twenty-five lactic acid bacteria were collected and identified (13). Lactobacillus casei was assessed for probiotic properties to fulfill the desirable criteria to be applied (Table 1).…”
Section: Microbiological Analysismentioning
confidence: 99%